B181 Block room: satisfaction and efficiency. (11th August 2022) - Silva, I; Barbosa Mendes, Â; Dias, R; Nunes, CS; Lages, N; Machado, H
Abstract : Background and Aims: The performance of regional anesthesia (AR) in a block room (BR) may have an impact on the efficiency of the Orthopedics operating room (OR). Our main goal is to evaluate the knowledge of healthcare professionals about AR and the BR Methods: Two types of surveys, previously validated at independent hospitals, were delivered to orthopedists and OR nurses. we performed a descriptive analysis of the variables. Results: A total of 126 surveys were filled out, 46 by orthopedists and 76 by OR nurses. It was observed that both physicians and nurses frequently recommend anesthetic techniques to their patients (39.1%/34.2%) and 50% of physicians and 44, 8% of nurses specify RA as the one to choose. Both groups consider that, compared to general anesthetics and intravenous analgesia, RA is safer (89.1%/69.7%) and associated with less sedation (95.6%/94.8%), better control of pain (95.7%/93.4%) and fewer side effects (63%/73.7%). Regarding patient satisfaction, both agreed that RA has better outcomes (84.7%/69.7%). They would choose RA for themselves (89.1%/89.5%) and recommend it to a family member (89.1%/92.1%). Speaking of BR, 80.4% of orthopedists agreed that it is associated with less time wasted in anesthetic preparation, higher productivity (65.2%) and greater efficacy (65.2%). Conclusions: We can conclude that most orthopedists and OR nurses recognized the various benefits of RA. Orthopedists agreed that BR is the key to allow RA to be used, improving outcomes and providing efficiency gains in the OR. Genuine support from the entire OR team could play a critical role in the change.